Using the "Flipped Classroom" Mixed Learning Model for the Formation of Phonetic and Phonological Competence - N. Kh. Sharipova; N. A. Kakhkhorova (International Journal on Orange Technologies, 2022)
The article deals with the problem of the formation of phonetic and phonological competence in teaching English in the context of modern FGOS and the potential of the model of mixed learning “Flipped Classroom" for the formation of this competence. The essence of phonetic and phonological competence, its relation to communicative competence and the reasons why this competence is important during English language teaching are revealed. The potential of the “Flipped Classroom” mixed learning model for the formation of phonetic and phonological competence and the implementation of new FGOS requests is identified and justified. The analysis of the features of this learning model is carried out; its advantages and disadvantages are revealed, as well as difficulties in implementing it into the educational process.